2004
DOI: 10.1172/jci22269
|View full text |Cite
|
Sign up to set email alerts
|

Human mitochondrial peptide deformylase, a new anticancer target of actinonin-based antibiotics

Abstract: Peptide deformylase activity was thought to be limited to ribosomal protein synthesis in prokaryotes, where new peptides are initiated with an N-formylated methionine. We describe here a new human peptide deformylase (Homo sapiens PDF, or HsPDF) that is localized to the mitochondria. HsPDF is capable of removing formyl groups from N-terminal methionines of newly synthesized mitochondrial proteins, an activity previously not thought to be necessary in mammalian cells. We show that actinonin, a peptidomimetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 56 publications
3
64
0
1
Order By: Relevance
“…In contrast, related compounds which are poorly lipophilic are only weakly active in cell proliferation assays despite good activity against the same class of aminopeptidases, e.g., CHR-79888. The evidence that the target for these effects lay within the cell focused attention on aminopeptidases, histone deacetylases, MetAP-2, or peptide deformylase as intracellular metalloenzyme targets (2,10,(24)(25)(26). CHR-2797 has been shown to be inactive against a number of these targets (histone deacetylase, MetAP-2) and/or to affect the proliferation of a different spectrum of tumor cell lines than inhibitors of some of these targets (histone deacetylase, peptide deformylase; refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, related compounds which are poorly lipophilic are only weakly active in cell proliferation assays despite good activity against the same class of aminopeptidases, e.g., CHR-79888. The evidence that the target for these effects lay within the cell focused attention on aminopeptidases, histone deacetylases, MetAP-2, or peptide deformylase as intracellular metalloenzyme targets (2,10,(24)(25)(26). CHR-2797 has been shown to be inactive against a number of these targets (histone deacetylase, MetAP-2) and/or to affect the proliferation of a different spectrum of tumor cell lines than inhibitors of some of these targets (histone deacetylase, peptide deformylase; refs.…”
Section: Discussionmentioning
confidence: 99%
“…CHR-2797 has been shown to be inactive against a number of these targets (histone deacetylase, MetAP-2) and/or to affect the proliferation of a different spectrum of tumor cell lines than inhibitors of some of these targets (histone deacetylase, peptide deformylase; refs. 25,26). That the target is most likely to be one or more members of the aminopeptidase class of metalloenzyme is indicated by the findings that (a) all active antiproliferative agents related to CHR-2797 were aminopeptidase inhibitors and (b) tumor cells that were sensitive to CHR-2797 were also sensitive to high concentrations of bestatin, a well-established, structurally distinct, aminopeptidase inhibitor (9).…”
Section: Discussionmentioning
confidence: 99%
“…In order to rule out that the observed effect of actinonin on mitochondrial DNA-encoded COX subunits was due to a possible unknown indirect effect following inhibition of APN, we treated cells with the APN inhibitor bestatin, which does not inhibit PDF (25). Bestatin did not have an effect on the COX or the complex II 70-kDa subunit levels.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the slow kinetic properties of HsPDF in an in vitro deformylation assay (24,29,35), we have shown that small interfering RNA (siRNA) interference of HsPDF decreases human cancer cell proliferation. Similarly, pharmacologic inhibition with the PDF antibiotic inhibitor actinonin and its analogs results in mitochondrial membrane depolarization and promotes cell death or proliferation arrest in a wide variety of cancer cell lines (18,25). However, the cellular function of HsPDF remains elusive, and others have proposed that it has none (29).…”
mentioning
confidence: 99%
“…Two PDFs have been identified in plants: mitochondrion-targeted PDF1A and PDF1B, which are targeted to both mitochondria and plastids (Giglione et al, 2000;Dirk et al, 2001). Only PDF1A has been found in humans and other animals (Giglione et al, 2000;Nguyen et al, 2003;Serero et al, 2003;Lee et al, 2004), and a PDF3 was identified in trypanosomatids (Bouzaidi-Tiali et al, 2007). Note that the many proteins encoded by the nuclear genome, which are further imported in the plastids, are not processed by the chloroplastic NME (cNME) but rather by a dedicated transit stromal peptidase.…”
Section: Introductionmentioning
confidence: 99%